Sweet’s syndrome: disease spectrum from an Indian perspective - Kaur, Sukhjot; Dhiman, Amit Kumar; Kaur, Sandeep; Narang, Vikram; Gupta, Sunil Kumar; Sood, Neena (International Journal of Research in Dermatology, 2017)
Background: Sweet’s syndrome is characterized by sudden onset of tender, erythematous papules, nodules, and plaques with a characteristic histopathology. It arises in three clinical settings- idiopathic, drug induced and malignancy induced. It has several clinical and histopathologic variants. Newer entities have been recently described in literature, thereby, emphasizing the need for continuous research. So, this study was conducted to add to scant data published in Indian literature with respect to this uncommon disease. The aims of the study were to bring insights into this rarely seen condition with special emphasis on histopathology; to highlight association of Sweet’s syndrome with other systemic diseases, and its extra-cutaneous manifestations. Methods: A retrospective analysis of medical records from January 2013 to February 2017 of patients with Sweet’s syndrome was done in our dermatology department in a tertiary care hospital. Results: Out of total 13 patients, 6 (46%) were males and 7 (54%) were females. The age of patients ranged from 33 to 82 years. Five (39%) had idiopathic Sweet’s syndrome, while 8 (61%) had non-idiopathic Sweet’s syndrome, out of which three were associated with autoimmune diseases (ulcerative colitis, interstitial lung disease and crohn’s disease in 1 patient each), 3 cases were associated with malignancy (chronic neutrophilic leukemia, chronic myeloid leukemia and acute myelogenous leukemia in 1 patient each) and 2 cases were linked with infection. Bullous Sweet’s syndrome was seen in 2 (15%) while neutrophilic dermatosis of dorsal hands was diagnosed in 5 (39%) cases. Four patients developed uncommon extracutaneous manifestations of Sweet’s syndrome. In addition to classical histopathological findings of Sweet’s syndrome, one case showed presence of immature neutrophils (histiocytoid Sweet’s syndrome), fibrinoid necrosis was evident in 2 (15.4%), leucocytoclasia in 6 (46.2%), RBC extravasation in 3 (23.1%) and neutrophilic infiltration into vessel wall in 3 (23.1%) patients. Conclusions: Several unique variants were observed in the current study.